Hippocampal sparing radiotherapy in adults with primary brain tumours: a comparative planning and dosimetric study using IMPT, IMRT and 3DCRT. (12th October 2019) - Patrice Aka, Fleman; Taylor, Roger; Hugtenburg, Richard; Lambert, Jamil; Powell, James
Abstract: Introduction: We assessed the feasibility of hippocampal sparing in adults with primary brain tumours using Intensity Modulated Proton Therapy (IMPT) and compared this with Intensity Modulated Radiotherapy (IMRT) and 3D-Conformal Radiotherapy (3DCRT). Methods and Materials: 20 patients were identified, and each patient underwent a radiotherapy planning CT scan and 2 MRI scans. A pre-operative diagnostic MRI scan was fused with the planning CT and used for target delineation and a dedicated 3T MRI scan at the time of planning was fused with the CT for hippocampus delineation. 3 hippocampal sparing plans were generated for each patient with specific prescriptions (54Gy/30 fractions, 60Gy/30 fractions and 59.4Gy/33 fractions) using IMPT, IMRT and 3DCRT. Hippocampal sparing was defined as median dose to contralateral hippocampus ≤25Gy without compromising target coverage and organ at risk dose constraints. Results: Hippocampal sparing was achieved in 19 patients (95%) with IMPT, 16 patients (80%) with IMRT and 13 patients (65%) with 3DCRT. The largest median hippocampal dose reduction was seen with IMPT, with a mean median hippocampal dose of 4.8Gy (range: 0.0Gy-24.9Gy), 14.6Gy (range: 1.9Gy-21.7Gy), and 16.2Gy (range: 2.3Gy-25.0Gy) for IMPT, IMRT and 3DCRT respectively. Hippocampal sparing IMPT failed in one case with the largest tumour volume (650cc) where 2/3 of the hippocampus overlapped the target volume. Conclusion: IMPT as compared to IMRT and 3DCRT plans showed a trend towards significant and effective hippocampal sparing in adult patients with primary brain tumours. We are currently evaluating this in a larger patient cohort and comparing IMPT with VMAT.